Snow White and the enormous turnip / [Big Books] - Robinson, Hilary; Sanfilippo, Simona (Wayland London, 2010)
Snow White loved to garden. She planted seeds every day. One of her turnips grew so big that it stuck in the ground. Snow White and the Seven Dwarves pulled and pulled, but it just wouldn't budge. Until, one day, a handsome prince came riding by